Image of the month: An unusual cause of cough, stridor and dyspnoea: A giant aortic arch aneurysm. Issue 3 (2021) - Singh, Bhupinder; Wander, Gurpreet S; Goyal, Abhishek; Chhabra, Shibba T; Aslam, Naved; Mohan, Bishav
No abstract available